2015
DOI: 10.1017/cjn.2014.127
|View full text |Cite
|
Sign up to set email alerts
|

Music is Beneficial for Awake Craniotomy Patients: A Qualitative Study

Abstract: Objectives: Patients undergoing awake craniotomy may experience high levels of stress. Minimizing anxiety benefits patients and surgeons. Music has many therapeutic effects in altering human mood and emotion. Tonality of music as conveyed by composition in major or minor keys can have an impact on patients' emotions and thoughts. Assessing the effects of listening to major and minor key musical pieces on patients undergoing awake craniotiomy could help in the design of interventions to alleviate anxiety, stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 40 publications
1
30
0
3
Order By: Relevance
“…Data of the study characteristics are shown in Table 1 . A total of fourteen case series [ 10 , 17 , 19 , 20 , 23 , 28 , 39 , 41 , 44 , 47 , 51 , 53 , 54 , 60 ] thirteen prospective studies [ 18 , 21 , 22 , 25 27 , 30 , 33 , 35 , 38 , 52 , 55 , 61 ], seventeen retrospective studies [ 24 , 29 , 31 , 34 , 37 , 40 , 42 , 43 , 45 , 46 , 48 50 , 57 59 , 62 ], two RCTs [ 32 , 56 ], and one pseudo-RCT [ 36 ] comprising 5945 AC procedures in 5931 patients were analysed ( Table 1 ). Of note, during the data extraction process it appeared that nine studies [ 20 , 22 , 27 , 31 , 42 46 ] partially repor...…”
Section: Resultsmentioning
confidence: 99%
“…Data of the study characteristics are shown in Table 1 . A total of fourteen case series [ 10 , 17 , 19 , 20 , 23 , 28 , 39 , 41 , 44 , 47 , 51 , 53 , 54 , 60 ] thirteen prospective studies [ 18 , 21 , 22 , 25 27 , 30 , 33 , 35 , 38 , 52 , 55 , 61 ], seventeen retrospective studies [ 24 , 29 , 31 , 34 , 37 , 40 , 42 , 43 , 45 , 46 , 48 50 , 57 59 , 62 ], two RCTs [ 32 , 56 ], and one pseudo-RCT [ 36 ] comprising 5945 AC procedures in 5931 patients were analysed ( Table 1 ). Of note, during the data extraction process it appeared that nine studies [ 20 , 22 , 27 , 31 , 42 46 ] partially repor...…”
Section: Resultsmentioning
confidence: 99%
“…Classical harmonic instrumental music in major or minor keys and in a moderate and calm mood are more suitable than expressive and fast music or pop and rock music. 11,63 Patients who preferred major keys liked the emotional feeling of the music. Patients who preferred minor keys chose it to alleviate their anxiety.…”
Section: Awake Craniotomy With Local Anesthesiamentioning
confidence: 99%
“…Patients who preferred minor keys chose it to alleviate their anxiety. 11 Because of extensive preoperative management, moderate sedation, and adequate local anesthesia, most patients who underwent awake craniotomy found it to be a positive experience. 64 Patients who underwent awake craniotomy had a positive short-term response and showed no signs of posttraumatic stress disorder.…”
Section: Awake Craniotomy With Local Anesthesiamentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Since 1991, the senior author has routinely performed awake craniotomy for intra-axial brain tumors with low complication rates and minimum resource utilization. [9,10,12,31] In 1996, a pilot study was initiated at the senior author's hospital in Toronto to assess the feasibility of performing craniotomy for tumor resection as an outpatient procedure. [13] The results of this study were reported in 2001.…”
Section: Home Carementioning
confidence: 99%